Prosedur Penerjemahan Foreignisasi dan Domestikasi Dalam Takarir Film “Im Westen Nichts Neues“ - Rafi Kurnia Widjaya; Rosyidah (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2025)
This article aims to describe the domestication and foreignization translation procedures used in Indonesian subtitles embedded in the film Im “Westen Nichts Neues”. This research makes an important contribution to the understanding of subtitle translation, and provides a basis for the use of foreignization and domestication procedures. The research was conducted using the descriptive qualitative method and the data was collected using the listen-read-write technique. The analysis technique used in this research is the Spradley model technique, which consists of four stages of analysis, namely domain analysis, taxonomic analysis, componential analysis, and cultural themes analysis. The research results show that the subtitle writer predominantly use the domestication procedure rather than foreignization. There are six translation techniques with domestication procedures that are most dominantly used by the subtitle writer, namely adaptation, transposition, modulation, amplification, reduction, and addition. These techniques were chosen to ensure the adaptation to the cultural context and space constraints of the subtitle so that the translation remains concise, clear, and has the same emotional impact as the original expression in the movie.